2010
DOI: 10.1308/147870810x12659688851393
|View full text |Cite
|
Sign up to set email alerts
|

Incarcerated lumbar hernia: a rare presentation

Abstract: This case illustrates the diagnostic uncertainty seen in lumbar herniation as a rare cause of large bowel obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…One case of bowel incarceration and a case of a strangulated hernia with bowel obstruction were mentioned. Light et al [38] reported on 20 cases of lumbar hernia in which incarcerated fat was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One case of bowel incarceration and a case of a strangulated hernia with bowel obstruction were mentioned. Light et al [38] reported on 20 cases of lumbar hernia in which incarcerated fat was observed.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 50 case reports [5, 26, 27, 34, 3885] regarding a primary lumbar hernia were included, describing 55 cases (see Table 4 for patient and study characteristics). In 49 patients, the location of the lumbar hernia was reported, and 34 (69.4%) occurred in the superior lumbar triangle, 12 (24.5%) in the inferior lumbar triangle, and 3 (6.1%) in both locations.…”
Section: Resultsmentioning
confidence: 99%
“…X-ray films may be usefull only in case of bowel obstruction as in our case, But CT and US can be applied to intestinal obstructions in which the origin is obscure [11-13]. …”
Section: Discussionmentioning
confidence: 99%
“…Superior lumbar hernia is more common than the inferior lumbar hernia 9. Regarding the clinical manifestation, the patients may present with a variety of signs and symptoms including mass/swelling in the flank area, lower back pain, and symptoms of bowel obstruction 3,10,14,15. Signs and symptoms of intestinal obstruction might also be present if a bowel loop has been incarcerated 10.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound may confirm the diagnosis when the swelling is palpable 12. Computed tomography scan played the vital role in defining hernia contents accurately 14,16,17. This coincides with our case report in which the ultrasound and magnetic resonance imaging had not confirmed the lumbar hernia.…”
Section: Discussionmentioning
confidence: 99%